FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG GO PUBLIK DI BEI - Bernadetta Monica Yulianingtyas, 11.05.52.0137; Nurhayati, Ida (Students Journal of Accounting and Banking, 2015)
Capital structure is a balance between the use of equity capital with the use of debt, which means how much equity and how much debt that will be used, so as to produce an optimal capital structure. This study aims to examine the effect of profitability, liquidity, non-debt tax shield, sales growth, business risk and the size of the company to the capital structure of the companies listed in Indonesia Stock Exchange (IDX) 2011-2013. The data used is the company went public in the period 2011- 2013. The researcher used purposive sampling and obtained a sample of 147 observation data. Analysis of data using multiple linear regression test. The results of this study showed that the profitability of a significant negative effect on capital structure. Liquidity significant negative effect on the capital structure of the company. Non-debt tax shield positive and significant impact on the capital structure of the company. Sales growth and a significant positive effect on the capital structure of the company. Business risk has no effect on the companys capital structure. The size of the company and a significant positive effect on the companys capital structure.Keywords: Profitability, Liquidity, Non-Debt Tax Shield, Sales Growth, Business Risk, Firm Size and Capital Structure